Prospective use of Ablation Index targets improves clinical outcomes following ablation for atrial fibrillation. (26th July 2017) - Hussein, Ahmed; Das, Moloy; Chaturvedi, Vivek; Asfour, Issa Khalil; Daryanani, Niji; Morgan, Maureen; Ronayne, Christina; Shaw, Matthew; Snowdon, Richard; Gupta, Dhiraj
Abstract: Aims: Late recovery of ablated tissue leading to reconnection of pulmonary veins remains common following radiofrequency catheter ablation for AF. Ablation Index (AI), a novel ablation quality marker, incorporates contact force (CF), time, and power in a weighted formula. We hypothesized that prospective use of our previously published derived AI targets would result in better outcomes when compared to CF‐guided ablation. Methods: Eighty‐nine consecutive drug‐refractory AF patients (49% paroxysmal) underwent AI‐guided ablation (AI‐group). AI targets were 550 for anterior/roof and 400 for posterior/inferior left atrial segments. Procedural and clinical outcomes of these patients were compared to 89 propensity‐matched controls who underwent CF‐guided ablation (CF‐group). All 178 procedures were otherwise similar, and both groups were followed‐up for 12 months. The last 25 patients from each group underwent analysis of all VisiTags™ for ablation duration, CF, Force‐Time Integral, and impedance drop. Results: First‐pass pulmonary vein isolation (PVI) was more frequent in AI‐group than in CF‐group (173 [97%] vs. 149 [84%] circles, P < 0.001), and acute PV reconnection was lower (11 [6%] vs. 24 [13%] circles, P = 0.02). Mean PVI ablation time was similar (AI‐group: 42 ± 9 vs. CF‐group: 45 ± 14 minutes, P = 0.14). Median impedance drop for AI‐group was significantly higher than in CF‐group (13.7 [9‐19] Ω vs. 8.8 [5.2‐13] Ω, P < 0.001). Two major complications occurred in CF‐group and none in AI‐group. Atrial tachyarrhythmia recurrence was significantly lower in AI‐group (15 of 89 [17%]) than in CF‐group (33 of 89 [37%], P = 0.002). Conclusion: AI‐guided ablation is associated with significant improvements in the incidence of acute PV reconnection and atrial tachyarrhythmia recurrence rate compared to CF‐guided ablation, potentially due to creation of better quality lesions as suggested by greater impedance drop.